A physics‐based threshold voltage model for hetero‐dielectric dual material gate Schottky barrier MOSFET. (17th January 2018) - Kumar, Prashanth; Bhowmick, Brinda
Abstract: This paper presents the analytical model of threshold voltage for hetero‐dielectric dual material gate Schottky barrier (SB) metal oxide semiconductor field effect transistor (MOSFET). The threshold voltage model is derived on the basis of the surface potential model. The threshold voltage is extracted using transconductance change method. The two‐dimensional surface potential, electric field, and threshold voltage model for the hetero‐dielectric dual material gate SB‐MOSFET are developed using 2‐D Poisson's equation, which satisfies the boundary conditions. Moreover, the model precisely depict the impact of hetero‐gate dielectric and gate oxide thickness on the surface potential, and threshold voltage of the hetero‐dielectric dual material gate SB and compared with single material gate SB‐MOSFET. Finally, a good agreement between the model results and numerical simulated results is achieved.